EFFECT OF TECHNICAL PARAMETERS TRACTION MOTORS FOR SAFETY CARRIAGE OF PASSENGERS - and (Municipal economy of cities. Series: «Economy science», 2013)
The questions provide an adequate level of electrical safety by monitoring the technical condition of isolation traction electric engine.